2005
DOI: 10.1016/j.appdev.2005.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Interracial contact and racial constancy: A multi-site study of racial intergroup bias in 3–5 year old Anglo-British children

Abstract: This paper examined the influence of interracial contact and racial constancy on the racial intergroup bias of young Anglo-British children. This multi-site study was conducted in areas of Great Britain that varied in terms of racial diversity. The study also investigated whether preschool children express bias on positive, but not negative, valence attributions. Anglo-British children (N = 136) between 3 and 5 years of age with different levels of interracial contact undertook a racial stereotype attribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 43 publications
3
99
1
1
Order By: Relevance
“…Developmental researchers have recently shown that contact between different social groups under certain conditions reduces childhood prejudice (e.g., Feddes, Noack, & Rutland, 2009;McGlothlin & Killen, 2006;McGlothlin, Killen, & Edmonds, 2005;Rutland, Cameron, Bennett, & Ferrell, 2005). For example, research has shown that, as children acquire cross-race friendships, prejudice is reduced (Crystal et al, 2008;McGlothlin & Killen, 2006) and adolescents are able to reject stereotypic expectations about others (due to their understanding that their friendship peers do not hold the negative qualities promoted in societal stereotypic images).…”
Section: Intergroup Contactmentioning
confidence: 99%
“…Developmental researchers have recently shown that contact between different social groups under certain conditions reduces childhood prejudice (e.g., Feddes, Noack, & Rutland, 2009;McGlothlin & Killen, 2006;McGlothlin, Killen, & Edmonds, 2005;Rutland, Cameron, Bennett, & Ferrell, 2005). For example, research has shown that, as children acquire cross-race friendships, prejudice is reduced (Crystal et al, 2008;McGlothlin & Killen, 2006) and adolescents are able to reject stereotypic expectations about others (due to their understanding that their friendship peers do not hold the negative qualities promoted in societal stereotypic images).…”
Section: Intergroup Contactmentioning
confidence: 99%
“…Cameron, Rutland, Brown & Douche 2006;Grutter & Meyer 2014;Rutland, Cameron, Bennett & Ferrell, 2005;Turner, Tam, Hewstone, Kenworthy et al, 2013). Many of the intergroup contact studies with children and adolescents have focused on testing the benefits of school desegregation on facilitating contact and reducing prejudice.…”
Section: Intergroup Contact and Social Harmonymentioning
confidence: 99%
“…Thus, in addition to our hypotheses about the influence of a numerical social consensus in object labeling and interracial social exclusions contexts, this study also explored the relevance of racial/ethnic group membership of the informants on young children's decisions in both contexts. Research on racial/ethnic group identification in young children has found that, from 3-4 years of age, children in racial/ethnic majority groups typically express a same-race (or "ingroup") preference, and implicit bias towards individuals from other groups ("outgroups") usually appears around 6 years of age as children gain knowledge about racial/ethnic stereotypes (Dunham, Baron, & Banaji, 2006;Enesco, Lago, Rodríguez, & Guerrero, 2011;Rutland, Cameron, Bennett, & Ferrell;.…”
Section: Introductionmentioning
confidence: 99%